KESIAPAN SEKOLAH TINGGI ILMU TARBIYAH (STIT) KOTA PAGAR ALAM DALAM IMPLEMENTASI KURIKULUM YANG MENGACU PADA KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) - Alip Kamaron (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
The issuance  of Presidential  Regulation  (Perpres)  of the Republic Indonesia Number  8 Year 2012  and  the Regula- tion of the Minister of Education and  Culture  (Permendikbud) Number  73 Year 2013,  requires  the University to redesign  the curriculum referring to the Indonesian Qualification  Framework (IQF). IQF is a framework of competency qualification  that can match,  equalize and integrate between  the field of education and the field of job training and work experience in the framework of giving recognition  of work competence in accordance with the structure of work in various sectors. This research  is to analyze,1). How is the readiness of the board  in the implementation of the curriculum to the IQF in Higher Education of Islamic Stud- ies (STIT) Pagar  Alam, 2). How is the readiness of lecturers in the implementation of curriculum  to IQF in Higher  Education of Islamic Studies  (STIT) Pagar  Alam and  3). How is the readiness of facilities and  infrastructure in the implementation of cur- riculum to IQF in Higher Education of Islamic Studies  (STIT) Pagar  Alam. Qualitative  method was used  in this research, data collection technique using interview, observation and  documentation. The results is showed  that readiness of the board  in the implementation of the curriculum  to IQF in Higher Education of Islamic Studies  (STIT) Pagar  Alam is still relatively low, it can be seen  from some  indicators  that 1). The management has never  attended a workshop,  training  on the preparation of IQF based  curriculum,  2). Never had any socialization regarding  curriculum to IQF, and 3). Do not have a guide for curriculum IQF. The readiness of lecturers in the implementation of curriculum to IQF in Higher Education of Islamic Studies (STIT) Pagar Alam is also still low and  not ready,  it can be seen from the lack of understanding of lecturers about  curriculum IQF, teaching  system which is conveyed by lecturers still tend to be conventional. In terms of facilities and infrastructure can be said is sufficient in the implementation of a curriculumIQF.